Uncovering the Use of Family-Centered Care Interventions Among Children With Cancer and Their Families: A Scoping Review of the Characteristics of Interventions and Effectiveness - Sijia Meng; Biyao Lu; Xiaofei Chen; Shuohui Chen (Journal of Family Nursing, 2026)
Family-centered care (FCC) interventions have gained increasing attention in pediatric oncology, yet their characteristics, effectiveness, and implementation challenges remain insufficiently synthesized. This scoping review systematically mapped existing FCC interventions for children with cancer and their families following JBI methodological guidance and the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) reporting standards. Twenty-two studies involving 1,049 pediatric patients and 1,504 family members were included. Interventions encompassed family empowerment programs, family-centered advance care planning, therapeutic conversations, functional support, and telehealth services, delivered via face-to-face, online, or hybrid formats. Evidence indicated improvements in psychological well-being, caregiver burden, and family quality of life. Despite methodological diversity, FCC interventions consistently demonstrated positive impacts. Future research should prioritize standardizing intervention components, integrating family systems theory, and developing culturally adaptable hybrid models to enhance clinical applicability and sustainability.